Overwinter and prespawning movements by a vulnerable freshwater pelagophilic minnow - Desiree M. Moore; Shannon K. Brewer (Scientific Reports)
Abstract The decline of pelagophil minnows is related to river fragmentation across the southern Great Plains landscape. Because we know little about pelagophil movement patterns and timing, we aimed to quantify the movements of the vulnerable Arkansas River shiner (ARS) during the winter (November–March) and prespawning (April–June) seasons. We tagged 4233 ARS using visible implant elastomer, passive integrated transponder, or p-Chip micro-transponder tags in 2018–2020. We sampled to recapture tagged fish weekly during the winter and biweekly during the spring. Tagged fish exhibited a downstream movement bias and movement was weakly related to increasing temperature, discharge, and photoperiod during winter, however most of the variability was explained by a random individual effect. Larger individuals moved greater distances than smaller fish. Upstream movements by a migratory portion of the population appeared to begin around late February based on the presence of fish at previously unoccupied sites. However, the first long-distance (30-km) upstream movement by a tagged fish was documented in late May. We show evidence that some ARS may be resident fish at sites throughout winter and spring of multiple years. To conserve freshwater pelagophil minnows, our results indicate water management strategies improving river connectivity in late winter through the spawning season may benefit spawning by migratory individuals, whereas lateral connectivity might benefit the resident portion of the population. Research efforts under experimental flows could provide insight to improved recovery options.